Exploring the intricate relationship between public debts and economic development in Nigeria - Christian Ugwueze Amu; Success Ikechi Kanu; Hilary Chinedu Akuwudike; Kingsley Ikechukwu Okere (Future Business Journal)
Abstract This study was carried out to ascertain the relationships between public debts and economic development in Nigeria. The specific objectives were to assess the effects of public debt on economic growth rate, aggregate demands, sectoral compositions and to find out if there exists any threshold relationship between debt accumulation and economic development in Nigeria. An ex-post facto research design was adopted in the study. With the aid of E-view statistical package, varied econometric analyses were conducted. Outcome of the study indicates that there exists a significant threshold relationship of between 50 and 60 percent for external debt, while a 15–17 percent threshold was established for domestic debt and debt accumulation in Nigeria. The study also reveals that external and domestic debts both have significant and largely negative impact on economic growth and development in Nigeria. The study therefore recommends that there is need for government at various levels in Nigeria to strive to reduce debt accumulation, especially in the long run by expanding her tax drag nets where necessary for overall and effective public financial management. There is also the need for a strong support for fiscal operations. Debt dependence in Nigeria was identified as a problem of fiscal federalism and claims to resource control among the federating units. It is also recommended that government must provide support for fiscal discipline. This could pave way for effective debt management practice in Nigeria.